2018
DOI: 10.1103/physrevlett.121.120602
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Work Extraction and Thermodynamics of Quantum Measurements and Correlations

Abstract: We analyze the role of indirect quantum measurements in work extraction from quantum systems in nonequilibrium states. In particular, we focus on the work that can be obtained by exploiting the correlations shared between the system of interest and an additional ancilla, where measurement backaction introduces a nontrivial thermodynamic tradeoff. We present optimal state-dependent protocols for extracting work from both classical and quantum correlations, the latter being measured by discord. Our quantitative … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(62 citation statements)
references
References 60 publications
2
58
0
Order By: Relevance
“…There has been much theoretical progress on understanding the role of entanglement for work extraction (see, e.g., Refs. [132][133][134][135][136][137]), mostly, however, for extracting work in idealized protocols. To the best of the author's knowlegde, a realizable and continuously working heat engine using quantum entanglement has not yet been presented.…”
Section: Entanglementmentioning
confidence: 99%
“…There has been much theoretical progress on understanding the role of entanglement for work extraction (see, e.g., Refs. [132][133][134][135][136][137]), mostly, however, for extracting work in idealized protocols. To the best of the author's knowlegde, a realizable and continuously working heat engine using quantum entanglement has not yet been presented.…”
Section: Entanglementmentioning
confidence: 99%
“…In order to give a map describing the quasi-static process, we extend the one developed in Ref. [50], where an isothermal processes for the case of a thermal reservoir were constructed by alternating infinitesimal adiabatic and isochoric steps (see also [54]). Let's assume the following sequence of CPTP maps…”
Section: Appendix B: Reversible Protocol With Cptp Mapsmentioning
confidence: 99%
“…Several works address the influence of coherence [12,14,15,27,28] and correlations [7,19,[29][30][31][32][33][34][35][36][37][38] in thermodynamic transformations in different scenarios. In * cerisola@df.uba.ar † augusto@df.uba.ar general, the creation of correlations is associated to some energetic cost and strategies to optimally extract work from them have been put forward [33][34][35][36][37][38]. On the other hand, it has been demonstrated that in the single-shot regime, by allowing auxiliary correlated catalytic systems [7] or correlations with catalytic systems [19], it is possible to enlarge the set of achievable transformations.…”
Section: Introductionmentioning
confidence: 99%